Priority directions of provision of stable land use - Hun’ko, L. (Land Management, Cadastre and Land Monitoring, 2017)
The conditions of stable land use are highlighted in this article. The question of the territory of agricultural enterprises is considered as well. The characteristic of the type of land use is given here. The recommendations are shown on the formation of ecologically safe types of land use. In the terms of new land relations is important to resolve the issue of land use regulation to with stand landscapes against adverse natural and anthropogenic influences. The main instrument of the state, which aims to provide an ecologically permissible and economically effective land use, land use is as an important component of land relations. Planning should include a system of legal, technical, economic and environmental activities that will ensure the preservation, restoration and rational use of land and other natural resources for the benefit of the whole society. Keywords: land use, land management, stable development, landscape, soil erosion, protection of land.